On L1 Interference and Reverse Transfer: Special Reference to the Concept of Multicompetence - El-dali, Hosni Mostafa (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
As well as the first language influences the second, the second language influences the first. Therefore, researchers have to focus not only on the L1’ L2, but also on the L2’ L1 effect. There has been extensive research into how L1 affects L2, commonly known as negative influence, but a lot less about the opposite direction, commonly known as Reverse or Backward transfer.The present study attempts to examine and critically review pertinent research into the question of bidirectional influence between languages. First, it traces the conceptual framework of the notion L1†’L2 effect. Second, it attempts to demonstrate how an emerging new language (L2) affects the existing L1. Although there are several ways of conceptualizing L2 influence on L1, the focus, in the present study, is on the concept of Multi-Competence proposed by Cook (1991; 1999; 2006; 2007; 2011) and how it shifts the evaluation angle of the interlanguage system. Third, it examines the pedagogical aspects of both directions, as manifested in L2 classroom. Special focus will be given to how the concept of multicompetence sees the goal of L2 learning and how language teaching should reflect such a goal. In addition, the advantages and disadvantages of using learners first language in L2 classroom will be highlighted and specific methodological recommendations will be made.